2014
DOI: 10.1093/toxsci/kfu147
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Aromatic Hydrocarbon Response of Human Bronchial Epithelial Cells Exposed to Petro- or Biodiesel Exhaust Treated with a Diesel Particulate Filter

Abstract: The composition of diesel exhaust has changed over the past decade due to the increased use of alternative fuels, like biodiesel, and to new regulations on diesel engine emissions. Given the changing nature of diesel fuels and diesel exhaust emissions, a need exists to understand the human health implications of switching to "cleaner" diesel engines run with particulate filters and engines run on alternative fuels like biodiesel. We exposed well-differentiated normal human bronchial epithelial cells to fresh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 47 publications
1
35
0
1
Order By: Relevance
“…Other direct deposition studies have also used mRNA transcripts as a proxy for cytokine production (Hawley et al, 2014a, b;Hawley and Volckens, 2013;Volckens et al, 2009;Lichtveld et al, 2012). Changes in IL-8 and COX-2 mRNA levels were measured using a QuantiTect SYBR Green RT-PCR kit (Qiagen) and QuantiTect primer assays for Hs_ACTB_1_SG (catalog no.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other direct deposition studies have also used mRNA transcripts as a proxy for cytokine production (Hawley et al, 2014a, b;Hawley and Volckens, 2013;Volckens et al, 2009;Lichtveld et al, 2012). Changes in IL-8 and COX-2 mRNA levels were measured using a QuantiTect SYBR Green RT-PCR kit (Qiagen) and QuantiTect primer assays for Hs_ACTB_1_SG (catalog no.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Compared to exposure of cells in culture media to resuspended particles, direct particle deposition likely provides a more biologically relevant exposure model and enhances sensitivity of cells to air pollution particle exposures (Volckens et al, 2009;Lichtveld et al, 2012;Hawley et al, 2014a, b;Zavala et al, 2014;Hawley and Volckens, 2013). The Electrostatic Aerosol in Vitro Exposure System (EAVES) used in this study deposits particles, generated in our outdoor photochemical chamber, directly onto lung cells by electrostatic precipitation (de Bruijne et al, 2009).…”
mentioning
confidence: 99%
“…13,17 There is also increasing evidence that, while the mass of particles produced by combusting biodiesel is typically less than that produced from identically combusting mineral diesel, the number concentration and surface area of particles may be greater, thereby producing more severe health effects. 11,23,24 This relationship is more apparent in studies employing older diesel engines, or engines without particulate filters, and has been controversially attributed to a greater amount of unburnt (or partially burnt) fuel in emissions from these engines. 1,25 In any study investigating the potential for exhaust emissions to impact health, the technology level of the engine is of critical importance.…”
Section: Physicochemical Properties Of Biodiesel Exhaustmentioning
confidence: 99%
“…In a similar study, Hawley and colleagues (2014) exposed normal human bronchial epithelial cells to exhaust from an engine using either mineral diesel or biodiesel of unspecified base oil. 23 Exposures were conducted for 5, 20 or 60 min over 2 days, and genes associated with oxidative stress and polycyclic aromatic hydrocarbon response (CYP1A1, HO-1, LDH) assessed 2 h later. The study found that all exposures increased responses, but that there were no significant differences between exposure groups.…”
Section: S Typhimuriummentioning
confidence: 99%
“…* p b 0.05 relative to HEPA filtered air control; ## p b 0.01 difference between the indicated groups. epithelial cells to exhaust from a diesel engine operated with and without a diesel particulate filter using the EAVES exposure system (Hawley et al, 2014b). A 60 min exposure to filtered and unfiltered exhaust induced similar levels of gene induction for CYP1A1.…”
Section: Discussionmentioning
confidence: 99%